2017
DOI: 10.1186/s12875-017-0638-9
|View full text |Cite
|
Sign up to set email alerts
|

How do population, general practice and hospital factors influence ambulatory care sensitive admissions: a cross sectional study

Abstract: BackgroundReducing unplanned hospital admissions is a key priority within the UK and other healthcare systems, however it remains uncertain how this can be achieved. This paper explores the relationship between unplanned ambulatory care sensitive condition (ACSC) admission rates and population, general practice and hospital characteristics. Additionally, we investigated if these factors had a differential impact across 28 conditions.MethodsWe used the English Hospital Episode Statistics to calculate the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
2
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 21 publications
4
39
2
11
Order By: Relevance
“…This study distinctively focuses on chronic ACSC hospitalizations. Prior studies using international definitions often combine both acute and chronic ACSC conditions, which may mask differential risk factors [5,10,71]. Canadian studies of chronic ACSC hospitalizations have identified rurality, immigrant status, lower income, smoking, underweight, and comorbidities as independent risk factors [16,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study distinctively focuses on chronic ACSC hospitalizations. Prior studies using international definitions often combine both acute and chronic ACSC conditions, which may mask differential risk factors [5,10,71]. Canadian studies of chronic ACSC hospitalizations have identified rurality, immigrant status, lower income, smoking, underweight, and comorbidities as independent risk factors [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the Canadian health system, hospitalizations for seven chronic ACSCs are routinely monitored, namely angina, asthma, congestive heart failure (CHF), chronic obstructive pulmonary disease (COPD), diabetes and diabetic complications, epilepsy, and hypertension [3]. Hospitalizations for chronic ACSCs may more specifically indicate insufficient disease management [4][5][6][7][8][9]. Studies have characterized risk factors for ACSC hospitalizations including demographics [10][11][12][13][14][15][16][17][18][19], rurality [5,17,[20][21][22][23][24][25][26], socioeconomic status (SES) [1,5,[15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38], chronic morbidities [10,16,17,…”
Section: Introductionmentioning
confidence: 99%
“…B. in Bezug auf systemimmanente und systemexterne Faktoren [8]. Initiale Analysen für Deutschland [1,10] berufen sich dabei auf die für das britische NHS-System entwickelte ASK-Klassifikation [6,11].…”
Section: Introductionunclassified
“…Bezüglich der Ursachen von ASK werden systemimmanente Faktoren zugangsseitig sowohl mit einer ungenügenden ambulanten Infrastruktur (z. B. Ärztedichte [12]), einem geringen Leistungsangebot [1] sowie im weiteren Sinne mit der Organisation des Krankenhaussektors begründet [1,11]. Qualitätseinbußen des ambulanten Bereichs können beispielsweise auf eine mangelnde Koordination zwischen den behandelnden Ärzten oder auf ein finanzielles Anreizsystem mit Auswirkungen auf die Behandlung zurückzuführen sein [8].…”
Section: Introductionunclassified
See 1 more Smart Citation